A Criminological Study of Motor Vehicle Traffic Violations by Children in the Parigi Moutong Police Resort Area - Marlena; Kamal; Titie (www.amertainstitute.com, 2025)
Motor vehicle traffic violations committed by minors represent a significant criminological and legal issue, particularly because they directly affect road safety and reflect the state's responsibility to provide legal protection for children. This study aims to examine the criminogenic factors underlying traffic violations committed by minors and to analyze preventive and control measures implemented by the Parigi Moutong Police Resort. An empirical legal research method was employed by integrating normative and sociological approaches. Primary data were collected through field observations and interviews with officers of the Traffic Unit (Satlantas) of Parigi Moutong Police Resort, while secondary data were obtained from statutory regulations and contemporary criminology literature. The findings reveal that traffic violations by minors are driven by internal factors—including emotional immaturity, impulsive behavior, sensation seeking, and low legal awareness—and external factors such as inadequate parental supervision, permissive social norms, peer group influence, and weak early-stage law enforcement. Police data from 2024 recorded 61,991 traffic incidents involving minors aged 15–17, indicating a critical public safety concern. Preventive efforts implemented by the police include legal education programs, traffic patrols, enforcement operations, ticketing, and targeted counseling for both minors and parents. This study concludes that traffic violations committed by minors should not be viewed merely as legal infractions but as a complex form of juvenile delinquency requiring comprehensive intervention from families, schools, communities, and law enforcement agencies to improve road safety and child protection.